X‐ray luminosity functions of different morphological and X‐ray type AGN populations. Issue 3 (1st March 2013) - Pović, M.; Pérez García, A.M.; Sánchez‐Portal, M.; Bongiovanni, A.; Cepa, J.; Fernández Lorenzo, M.; Lara‐López, M.A.; Gallego, J.; Ederoclite, A.; Márquez, I.; Masegosa, J.; Alfaro, E.; et al.
Abstract Luminosity functions are one of the most important observational clues when studying galaxy evolution over cosmic time. In this paper we present the X‐ray luminosity functions for X‐ray detected AGN in the SXDS and GWS fields. The limiting fluxes of our samples are 9.0 ×10–15 and 4.8 ×10–16 erg cm–2 s–1 in the 0.5–7.0 keV band in the two fields, respectively. We carried out analysis in three X‐ray bands and in two redshift intervals up to z ≤ 1.4. Moreover, we derive the luminosity functions for different optical morphologies and X‐ray types. We confirm strong luminosity evolution in all three bands, finding the most luminous objects at higher redshift. However, no signs of density evolution are found in any tested X‐ray band. We obtain similar results for compact and early‐type objects. Finally, we observe the "Steffen effect", where X‐ray type‐1 sources are more numerous at higher luminosities in comparison with type‐2 sources. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)